Label-free and non-destructive identification of naïve and primed embryonic stem cells based on differences in cellular metabolism. (February 2023) - Koo, Kyeong-Mo; Go, Young-Hyun; Kim, Seong-Min; Kim, Chang-Dae; Do, Jeong Tae; Kim, Tae-Hyung; Cha, Hyuk-Jin
Abstract: Pluripotent stem cells (PSCs) exist in naïve or primed states based on their origin. For in vitro culture, these PSCs require different supplements and growth factors. However, owing to their similar phenotypic features, identifying both cell types without harming cellular functions is challenging. This study reports an electrochemical method that enables simple, label-free, and non-destructive detection of naïve embryonic stem cells (ESCs) derived from mouse ESCs, based on the differences in cellular metabolism. Two major metabolic pathways to generate adenosine triphosphate (ATP)—glycolysis and oxidative phosphorylation (OXPHOS)—were blocked, and it was found that mitochondrial energy generation is the origin of the strong electrochemical signals of naïve ESCs. The number of ESCs is quantified when mixed with primed ESCs or converted from naïve–primed switchable metastable ESCs. The mouse PSCs derived from doxycycline-inducible mouse embryonic fibroblasts (MEFs) are also sensitively identified among other cell types such as unconverted MEFs and primed PSCs. The developed sensing platform operates in a non-invasive and label-free manner. Thus, it can be useful in the development of stem cell-derived therapeutics. Graphical abstract: Image 1